Plasma turbulence in localized sheared flows - Chirkov, A.Yu (Вопросы атомной науки и техники, 2007)
Plasma configurations with strong velocity shear are considered taking into account magnetic shear. Ion temperature gradient driven drift instability and Kelvin-Helmholtz type instability are analyzed for such sheared plasma flows. Possible instability saturation mechanisms and estimation of particle diffusivity are discussed.